2010
DOI: 10.3109/02699052.2010.494590
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality-of-life and life satisfaction 6–15 years after traumatic brain injuries in northern Sweden

Abstract: These results confirm the importance of TBI as a cause of long-term disability and the impact of the injury on the individuals' self-perceived values of health, quality-of-life and life satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 48 publications
11
74
2
1
Order By: Relevance
“…A previous report has shown that it is most important to have a nation-specific reference group, as cultural differences may have an impact on life satisfaction scores. 22 The reference groups comprised Swedish populations between the ages of 18-64 years 10 and 27-71 years, 13 respectively. Hence, these control groups were younger but equal in gender distribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous report has shown that it is most important to have a nation-specific reference group, as cultural differences may have an impact on life satisfaction scores. 22 The reference groups comprised Swedish populations between the ages of 18-64 years 10 and 27-71 years, 13 respectively. Hence, these control groups were younger but equal in gender distribution.…”
Section: Discussionmentioning
confidence: 99%
“…To compare the results (seven-point scale) with the reference sample (five-point scale), scores were recoded as 1 = 1; 2 and 3 = 2; 4 = 3; 5 and 6 = 4; and 7 = 5 as seen in a previous study. 12,13 Neurological deficits Neurological deficits, T1-S5, were graded according to the American Spinal Injury Association (ASIA) impairment scale (AIS) in patients discharged with permanent SCI from hospital: AIS A, complete, no motor or sensory function is preserved in the sacral segments S4-S5; AIS B, incomplete, sensory but not motor function is preserved below the neurological level and includes the sacral segments S4-S5; AIS C, incomplete, motor function is preserved below the neurological level, and more than half of key muscles below the neurological level have a muscle grade o3; AIS D, incomplete, motor function is preserved below the neurological level, and at least half of key muscles below the neurological level have a muscle grade of 3 or more. The neurological deficits in each patient were re-scrutinized and re-assessed after evaluation of the respective patient records by a specialist in neurology.…”
Section: Life Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vários estudos têm revelado que as pessoas com LCA reportam níveis de QdV mais baixos do que a população em geral (Gordon et al, 2006;Jacobsson, Westerberg, & Lexell, 2010;Man et al, 2004;Nestvold & Stavem, 2009;Teasdale & Engberg, 2005), sendo evidente a necessidade de a reabilitação neuropsicológica promover a reintegração social e vocacional, de forma a aumentar a QdV dos indivíduos (Tomberg, Toomela, Pulver, & Tikk, 2005). O bem-estar após LCA parece ser determinado por uma grande variedade de fatores como o grau de autonomia , o estado emocional (Corrigan, Smith, & Granger, 1998;Koskinen, 1998), a capacidade física (Chandrashekar & Benshoff, 2007;Mailhan et al, 2005), o nível de participação social na comunidade (Pierce & Hanks, 2006) e o regresso ao emprego (Tomberg, Toomela, Ennok, & Tikk, 2007).…”
Section: Impactos Da Reabilitação Neuropsicológica Na Qdvunclassified
“…Similar to adult TBI, prediction of outcome in survivors is described to be complex, with several factors like the injury severity [27,28], rehabilitation and social support interacting to determine the extent of residual impairments [28]. Anatomic variances to adults like a disproportional large and heavy head with weak neck muscles as well as greater flexibility of cranial bones minimize focal brain injuries but increase the risk of diffuse brain injuries [20,[29][30][31][32][33][34][35][36].…”
Section: Paediatric Tbimentioning
confidence: 99%